Effect of cell-free fetal DNA on spontaneous preterm labor - Rogaye Darghahi; Novshin Mobaraki-Asl; Zahra Ghavami; Farhad Pourfarzi; Saied Hosseini-Asl; Faranak Jalilvand (Wolters Kluwer Medknow Publications, 2019)
Inflammatory phenomenon, including cell-free fetal DNA (cffDNA), is one of the various causes of preterm delivery. Always, there is a trend in the prediction and prevention of preterm labor. Herein, the aim of this study is to assess the value of cffDNA levels in serum of pregnant women for prediction of spontaneous preterm labor. A case-control study with nonrandomized convenience sampling was conducted. One hundred women qualifying for the study were enrolled. The participants were divided into two groups of healthy nulliparous pregnant women (n = 50) and nulliparous pregnant women experiencing preterm labor (n = 50). Then, venous blood was sampled from each participant and its plasma was separated and analyzed. The mean age of women in the experimental group was 22.90 years with the standard deviation of 4.04, while in the control group these two values were 23.78 and 4.37, respectively. In the experimental group, 29 patients (58%), and in the control group, 27 patients (54%) had cffDNA. The mean of the counted DNA in the experimental group was 2080/03 with the standard deviation of 909/792 while the same values for the control group were 1183/26 and 620/720, in the same order. The statistical analysis revealed that this difference was meaningful at P = 0.001. Furthermore, in the experimental group, cffDNA increased with increase in the age and the difference was meaningful. Finally, increasing pregnancy age in the experimental group led to an increase in the number of cffDNA (P = 0.001). The results of this study indicated that the cumulative frequency of preterm labor for women with positive cffDNA was significantly higher. High levels of cells' DNA in the serum of pregnant mothers increase the risk of spontaneous preterm labor. These observations may have implications for preterm labor.